(untitled) (Revista científica Olimpia, 2020)
Interpersonal relationships are long-term partnerships between two or more people. These associations can be based on emotions and feelings, such as love and artistic taste, interest in business and social activities, interactions and collaborative forms at home. They take place in a wide variety of contexts, such as family, groups of friends, marriage, friendships, work environments, social and sports clubs, neighborhood settings, religious communities. They can be regulated by law, by custom or by mutual agreement, and they are a fundamental base or network of social groups and society as a whole. They play a fundamental role in the integral development of people. Through them, the individual obtains important social reinforcements from the immediate environment, which favors their adaptation and integration to the same. It is important to take into account the most relevant values ​​in order to better favor interpersonal relationships.In the investigation, interpersonal relationships are treated, based on the criteria of several authors. Be part of a psychodiagnostic so several instruments were applied. The following methods were used: Historical-Logical, Inductive - Deductive, Analysis - synthesis, Observation, Survey, Interview. The intentional sample that will be constituted by 10 athletes of the EIDE school basketball team "Captain Orestes Acosta Herrera" of Santiago de Cuba, these in turn constitute the total population. Subsequently, the results will be analyzed through the descriptive statistics and the electronic tab of Excel and thus establish the psycho-pedagogical actions.